Pratiques Traditionnelles de Conservation de la Nature à L’épreuve des Faits Chez Les Peuples Riverains de la Réserve de Biosphère de Yangambi (RDC) - Koy, Justin Kyale; Ngonga, Alphonse Maindo Monga (European Scientific Journal, ESJ, 2017)
The Riparian people of the Biosphere Reserve of Yangambi (Turumbu and Bamanga) have traditionally developed practices of nature conservation. However, the ongoing socio-cultural changes in the region are likely to affect the sustainability of those practices. On one hand, this study aims to identify the Turumbu and Bamanga’s existing traditional practices and knowledge about conservation. On the other hand, it aims to analyze the socio-cultural changes on their sustainability. Data collection techniques comprised of historical archives exploitation, focus-group, and individual interviews conducted for 20 villages surrounding the Biosphere Reserve of Yangambi (BRY). Investigations revealed a huge range of practices affecting plant communities and wildlife species as well as natural phenomena restricting either hunting or fishing activities. Findings also pointed out traditional knowledge and mystical-based considerations from agricultural practices. In addition, cemeteries, sites for the rites of passage, the food-based taboos, and legendary sites were target to sacralisation. The grafting between religion, colonization, modernity and culture, resulted to a bottleneck which affects such practices. In spite of these constraints, the study shows that there are still opportunities at the multilevel (local, national, global) for their reactivation.